Validation of the European Society of Cardiology 0/1-hour algorithm for chest pain triage in Asian emergency departments: a multinational stepped-wedge cluster-randomised trial - Inoue, Kenji; Twerenbold, Raphael; Kasim, Sazzli; Salleh, Farina Mohd; Mohamed, Ahmad Suhailan; Tan, Jack Wei Chieh; Lim, Xin Yi; Ping, Ting Boon; Ahmad, Bakhtiar; Idrose, Alzamani Mohammad; Phrommintikul, Arintaya; Suwannasom, Pannipa; et al. (Heart, 2025)
Background Rapid triage of patients presenting with chest pain is essential for early diagnosis and safe disposition. The European Society of Cardiology (ESC) 0/1-hour hs-cTn algorithm has shown promising performance in Western cohorts, but evidence supporting its implementation in diverse Asian emergency department (ED) settings remains limited. Therefore, we evaluated the safety and clinical utility of the ESC 0/1-hour algorithm for chest pain triage across multiple Asian EDs. - Methods This was a prospective, stepped-wedge, cluster-randomised trial conducted across 12 hospitals in five Asian countries, enrolling 3869 patients with suspected acute coronary syndrome without ST elevation (NSTE-ACS). Usual care involved troponin testing without standardised timing, whereas the 0/1-hour protocol followed ESC recommendations using high-sensitivity cardiac troponin T testing at baseline and 1 hour. The primary endpoint was 30-day major adverse cardiac events (MACE), including cardiovascular death, myocardial infarction (MI) and unplanned revascularisation. Non-inferiority was assessed using a one-sided 95% CI with a margin of 1.5%. - Results Of 3869 patients (2059 usual care; 1810 0/1-hour care), MACE occurred in 1.7% of usual care patients and 1.4% in the 0/1-hour care (upper one-sided 95% CI -0.3%), confirming non-inferiority. ED discharge rates were significantly higher with the 0/1-hour algorithm (60% vs 35%, p<0.001). Among 941 patients classified as low risk group, MACE occurred in only 3 patients, including one cardiovascular death and two unplanned revascularisations; no non-fatal MIs were reported. - Conclusion The ESC 0/1-hour algorithm is safe and effective for rapid triage of chest pain in Asian EDs. These findings provide external validation of the 0/1-hour algorithm and support broader global implementation. - Trial registration number UMIN000042461.
Vorab online veröffentlicht: 23. November 2025
Gesehen am 29.01.2026